G194 Step-up to consultant: innovative simulation preparing trainees for the consultant role. (25th October 2020) - Winter, R; Magnus, D
Abstract : Background: The transition from paediatric trainee to consultant has long been acknowledged as challenging. The RCPCH has implemented the START assessment and 'Stepping Up' programme to address this, but senior paediatric trainees remain apprehensive about their first consultant roles. When surveyed, they express particular concern about decisions trainees rarely get to practice, such as stopping CPR, managing junior colleagues and being on call from home. Aims: Design a simulation-based education programme to prepare general and subspecialty paediatric trainees for the consultant role. Methods: We conducted thematic analysis of trainee concerns from a 2017 RCPCH conference survey. These themes were developed into a framework of six domains which described different aspects of the consultant role: leader, educator, nurturer, juggler, negotiator and communicator. We designed challenging scenarios to test these domains, relevant to all trainees, and delivered two days of simulation-based education to 11 ST6-8 candidates. Given the high degree of difficulty, we recruited a specialist consultant-heavy faculty and took steps to protect candidates' psychological safety. Our programme included simulation innovations such as waking candidates with an overnight phone call, managing multiple clinical areas simultaneously and balancing clinical and non-clinical pressures. Results: 10 of 11 candidates gave us feedback, with 10/10 reporting they felt significantly more confident and competent to perform as consultants. 9/10 candidates felt simulation was superior to all other methods in preparing for difficult aspects of the consultant role. 6 candidates later approached us independently to report that they felt our course was more useful than the RCPCH START assessment. Conclusions: We have demonstrated that simulation is an effective tool to prepare senior trainees for transition to the consultant role. We intend to run this course on a regular basis for interested senior trainees across the UK.